Defect states in LiFeAs as seen by low‐temperature scanning tunneling microscopy and spectroscopy. Issue 1 (20th June 2016) - Schlegel, R.; Nag, P. K.; Baumann, D.; Beck, R.; Wurmehl, S.; Büchner, B.; Hess, C.
Abstract: We present a microscopic investigation of frequently observed impurity‐induced states in stoichiometric LiFeAs using low‐temperature scanning tunneling microscopy and spectroscopy (STM/STS). Our data reveal seven distinct well‐defined defects which are discernible in topographic measurements. Depending on their local topographic symmetry, we are able to assign five defect types to specific lattice sites at the Li, Fe, and As positions. The most prominent result is that two different defect types have a remarkably different impact on the superconducting state. A specific and quite abundant Fe‐defect with D 2 ‐symmetry generates significant impurity‐induced additional states primarily at positive bias voltage with pronounced peaks in the on‐site local density of states (LDOS) at about 4 and 12 mV. On the other hand, a D 4 ‐symmetric As‐defect causes a significantly enhanced LDOS at both positive and negative bias voltages. We expect that these findings provide fresh input for further experimental and theoretical studies on elucidating the nature of superconductivity in LiFeAs.